T Cell Receptor Expression Timing and Signal Strength in the Functional Differentiation of Invariant Natural Killer T Cells - Dashtsoodol, Nyambayar; Bortoluzzi, Sabrina; Schmidt-Supprian, Marc (Frontiers in Immunology, 2019)
The CD1d-restricted Vα14 invariant NKT (iNKT) cell lineage in mice (Vα24 in humans) represents an evolutionary conserved innate-like immune cell type that recognize glycolipid antigens. Because of their unique ability to promptly secrete copious amounts of both pro-inflammatory and anti-inflammatory cytokines, typically produced by different T helper cell types, iNKT cells are implicated in the regulation of various pathologic conditions such as infection, allergy, autoimmune disease, maintenance of transplantation tolerance and cancer. This striking multifaceted role in immune regulation is correlated with the presence of multiple functionally distinct iNKT cell subsets that can be distinguished based on the expression of characteristic surface markers and transcription factors. However, to date it remains largely unresolved how this puzzling diversity of iNKT cell functional subsets emerges and what factors dictate the type of effector cell differentiation during the thymic differentiation considering the mono-specific nature of their TCR and their selecting molecule CD1d. Here, we summarize recent findings focusing on the role of TCR-mediated signaling and discuss possible mechanisms that may influence the sublineage choice of iNKT cells.